Flexible query answering systems : 12th International Conference, FQAS 2017, London, UK, June 21-22, 2017, Proceedings /: 12th International Conference, FQAS 2017, London, UK, June 21-22, 2017, Proceedings. (2017) - Unknown
No abstract available